PEMBELAJARAN ENGLISH PRONUNCIATION MELALUI MOBILE ASSISTED LANGUAGE LEARNING (MALL): POTENSI DAN HAMBATAN - Poppy Sofia Hidayati; Abdul Rosyid (Pedagonal : Jurnal Ilmiah Pendidikan, 2020)
TOWARD MALL IN LEARNING ENGLISH PRONUNCIATION: POTENTIALS AND PITFALLS In this era of technology, the use of mobile phone, which is wireless, personal, networking, and ubiquitous have influenced every aspect of human life. Using mobile technology in language learning would give opportunity to learn outside the conventional class and decrease English learning problems in EFL setting. By using mobile phone, the learners could access information and develop it across space, be connected to the others and explore their ability more. This study aimed at investigating the use of Mobile Assisted Language Learning (MALL) in learning English Pronunciation. This study was qualitative approach which employed case study as the method. The study involved 30 students English Education Study Program. The data are gathered from observation, questionnaire, and Focused Group Discussion (FGD). The result shows that the use of MALL has benefited the students in enhance their ability in English Pronunciation through ELSA Speak application. The pitfalls mostly lay in the problems of signal and network in the learning process. Thus, MALL should be integrated in learning English process since it is perceived to be useful to enhance students’ performance in learning English.